Narcolepsy Features in Young Patients - Govi, Annamaria; Antelmi, Elena; Pizza, Fabio; Ingravallo, Francesca; Plazzi, Giuseppe (Journal of Pediatric Biochemistry, 2016)
Narcolepsy is a lifelong central hypersomnia characterized by excessive daytime sleepiness, cataplexy, sleep paralysis, hypnagogic hallucinations, and disrupted nocturnal sleep. Behavioral and psychiatric comorbidities are often associated clinical features. It is divided into two subtypes, narcolepsy type-1, and narcolepsy type-2, depending on the presence of cataplexy and the cerebrospinal fluid hypocretin-1 levels. An autoimmune process, along with environmental factors, has been hypothesized to cause the disease. Among children and adolescents, incidence in Europe falls between 0.14 and 0.3 in 100,000, with a reported increase in the incidence after the 2009 H1N1 pandemic influence and vaccination. Currently, specific pediatric diagnostic criteria and cut-off instrumental values are lacking. Clinical presentation of the disease may differ between children and adults, and misdiagnoses or diagnostic delays are still an issue. The treatment is based on behavioral and pharmacological therapy, but drugs in children are prescribed off-label. Overall, pathogenic mechanism of narcolepsy and data on drug efficacy in children are still limited: more research is needed to develop new drugs and to reach approval of current treatments in the pediatric population.
Keywords: children; sleep; sleepiness; cataplexy; cataplectic facies